Defekti preddvornega pretina - Klemen, Luka (Medicinski razgledi, 2008)
Atrial septal defect (ASD) is one of the most common congenital heart diseases. It is an opening in the interatrial septum that permits shunting of blood between the left and right atrium, thus leading to right heart volume overload. Four types of ASD are recognized, with ASD type secundum being the most frequent. Patients remain asymptomatic for many years and may be first diagnosed in adulthood. The symptoms of ASD are nonspecific, but typical auscultatory findings or a pathological electrocardiogram or chest X-ray may draw attention to the diagnosis. Echocardiography is the method of choice for the diagnosis of ASD. It enables the doctor to establish the presence of the defect, its location and hemodynamic significance, as well as other associateddefects. All hemodynamically significant defects require closure. Percutaneous closure using special devices is the therapy of choice in appropriate cases of ASD type secundum, whereas all other defects require surgical closure.
Keywords: Ehokardiografija; Heart Septal Defects, Atrial; Srce, pretin, defekti preddvorni; Classification; Diagnosis; Elektrokardiografija; Therapy; Srce, kateterizacija; srce; heart; Electrocardiography; preddvor; Thoracic Radiography; Echocardiography; defekti; Heart Catheterization; zdravljenje; diagnostika